2019
DOI: 10.1021/acsami.8b19679
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanocluster-Decorated Nanocomposites with Enhanced Emission and Reactive Oxygen Species Generation

Abstract: Ligand-protected gold nanoclusters (AuNCs) show promise for high performance in biological applications, such as imaging and therapeutics. The assembly of AuNCs with biological macromolecules represents a simple but effective approach to fine-tuning of material functionalities. Thus, these materials might enable intracellular applications of AuNCs. Herein, we prepared a new AuNC-based nanometric system through a self-assembly approach mediated by hydrophobic and electrostatic effects. We show that hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 59 publications
(86 reference statements)
1
58
0
Order By: Relevance
“…19A). 106 Results of in vitro experiments revealed that the AuNC-HA-PROT nanocomposite showed effective endocytosis of target MDA-MB-231 cancer cells, high PDT activity, as well as uorescence imaging.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…19A). 106 Results of in vitro experiments revealed that the AuNC-HA-PROT nanocomposite showed effective endocytosis of target MDA-MB-231 cancer cells, high PDT activity, as well as uorescence imaging.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…Isothermal microcalorie data for titration of AuNCs solution with (b) HA and (c) PROT. Reprinted with permission from ref ( 29 ). Copyright 2019 American Chemical Society.…”
Section: Regulating the Optical Properties Of A Gold Nanoclustermentioning
confidence: 99%
“… 10 We prepared therapeutic nanocomposites based on AuNCs with enhanced ROS generation. 29 Owing to the specific binding between HA and CD44, the nanocomposites based on AuNCs could serve as efficient photosensitizers to kill MDA-MB-231 cancer cells. Derived from robust ability to adsorb and scatter X-ray, structurally defined gold-levonorgestrel nanoclusters were demonstrated as radiosensitizers for cancer therapy.…”
Section: Employing the Optical Properties For Biomedical Applicationsmentioning
confidence: 99%
“…Peaks at 3000–3500 cm −1 confirmed the presence of OH/N–H bonds, and three peaks at 1617, 1566, and 1436 cm −1 confirmed the presence of C O, C C, and C–N bonds, respectively. 27 Moreover, C–N stretching of the amides peak was observed at 1376 cm −1 . 28 Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We conjectured that CDs generate ROS under UV light illumination. 27 The DCFH could be rapidly oxidized by ROS and lead to the formation of highly fluorescent 2′,7′-dichlorofluorescein (DCF) species. 29 The ROS generated from CDs under UV light irradiation could be verified by monitoring the DCF fluorescence signal (Fig.…”
Section: Resultsmentioning
confidence: 99%